Improved Simulation of Edaphic and Manure Phosphorus Loss in SWAT. Issue 4 (1st July 2016) - Collick, Amy S.; Veith, Tamie L.; Fuka, Daniel R.; Kleinman, Peter J.A.; Buda, Anthony R.; Weld, Jennifer L.; Bryant, Ray B.; Vadas, Peter A.; White, Mike J.; Harmel, R. Daren; Easton, Zachary M.
Abstract : Watershed models such as the Soil Water Assessment Tool (SWAT) and the Agricultural Policy Environmental EXtender (APEX) are widely used to assess the fate and transport of agricultural nutrient management practices on soluble and particulate phosphorus (P) loss in runoff. Soil P‐cycling routines used in SWAT2012 revision 586, however, do not simulate the short‐term effects of applying a concentrated source of soluble P, such as manure, to the soil surface where it is most vulnerable to runoff. We added a new set of soil P routines to SWAT2012 revision 586 to simulate surface‐applied manure at field and subwatershed scales within Mahantango Creek watershed in south‐central Pennsylvania. We corroborated the new P routines and standard P routines in two versions of SWAT (conventional SWAT, and a topographically driven variation called TopoSWAT) for a total of four modeling "treatments". All modeling treatments included 5 yr of measured data under field‐specific, historical management information. Short‐term "wash off" processes resulting from precipitation immediately following surface application of manures were captured with the new P routine whereas the standard routines resulted in losses regardless of manure application. The new routines improved sensitivity to key factors in nutrient management (i.e., timing, rate, method, and form of P application). Only the new P routines indicated decreases in soluble P losses for dairy manure applications at 1, 5, and 10 d before a storm event. The new P routines also resulted in more variable P losses when applying manure versus commercial fertilizer and represented increases in total P losses, as compared with standard P routines, with rate increases in dairy manure application (56, 000 to 84, 000 L ha −1 ). The new P routines exhibited greater than 50% variation among proportions of organic, particulate, and soluble P corresponding to spreading method. In contrast, proportions of P forms under the standard P routines varied less than 20%. Results suggest similar revisions to other agroecosystem watershed models would be appropriate. Core Ideas: Dynamic manure P routines were added to the conventional SWAT model. New P routines were corroborated in two versions of SWAT. New P routines accurately simulated the 4R effects of manure management.